Getting it right in the esthetic zone! - Kamal Kiswani; Deepinder Duggal; Poonam Rohra (Wolters Kluwer Medknow Publications, 2012)
Introduction of osseointegration by Branemark and coworkers and replacement of missing teeth by implants has revolutionized oral rehabilitation. As a result, restoration of form and function has shown a paradigm shift. Implant-supported restorations in completely or partially edentulous patients have proven to be highly predictable in numerous studies. Patients increasingly demand prosthesis that are not only functional but are equally esthetic; hence, implants placed in the anterior esthetic zone, pose a huge challenge. At times thorough planning and diligent execution can spare the patient from elaborate procedures of grafting. One such case report of restoring the esthetic zone in a female patient has been reported here with a 5-year follow-up.